2019
DOI: 10.1016/j.scr.2019.101427
|View full text |Cite
|
Sign up to set email alerts
|

An induced pluripotent stem cell line (TRNDi006-A) from a MPS IIIB patient carrying homozygous mutation of p.Glu153Lys in the NAGLU gene

Abstract: Mucopolysaccharidosis type III B (MPS IIIB) is a lysosomal storage disorder caused by mutations in the NAGLU gene encoding N -acetylglucosaminidase. Here, we report the generation of a human induced pluripotent stem cell (iPSC) line from dermal fibroblasts of a MPS IIIB patient. The iPSC line has homozygous mutations of G > A transversion at nucleotide 457 of the NAGLU gene (457G > A), resulting in the substitution of lysine for glutamic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Although no in vitro human neural model has been generated for Sanfilippo A, recently, it has been reported that the generation of two lines of iPSCs from fibroblasts of the same patient [ 58 ] could be used for the generation of these models. In the case of Sanfilippo B, new iPSC lines from patient fibroblasts have also been generated [ 59 , 60 ].…”
Section: Disease Modelsmentioning
confidence: 99%
“…Although no in vitro human neural model has been generated for Sanfilippo A, recently, it has been reported that the generation of two lines of iPSCs from fibroblasts of the same patient [ 58 ] could be used for the generation of these models. In the case of Sanfilippo B, new iPSC lines from patient fibroblasts have also been generated [ 59 , 60 ].…”
Section: Disease Modelsmentioning
confidence: 99%